Thalassemia and hemoglobinopathy prevalence in a community-based sample in Sylhet, Bangladesh - Wendt, Amanda; Brintrup, Joaquin; Waid, Jillian; Kader, Abdul; Lambrecht, Nathalie J.; Gabrysch, Sabine (Orphanet journal of rare diseases, 2023)
Inherited blood disorders affect 7% of the population worldwide, with higher prevalences in countries in the “thalassemia belt,” which includes Bangladesh. Clinical management options for severely affected individuals are expensive; thus, targeted government policies are needed to support prevention and treatment programs. In Bangladesh, there is a lack of data, in particular community-based estimates, to determine population prevalence. This study aims to estimate the prevalence of a wide range of hemoglobinopathies and their associations with anemia in a community-based sample of women and young children in rural Sylhet, Bangladesh.